Wind tunnel investigation of the ability of drift-reducing nozzles to provide mitigation measures for bystander exposure to pesticides. (February 2021) - Butler Ellis, M. Clare; Lane, Andrew G.; O'Sullivan, Christine M.; Jones, Steven
Abstract : Models recently developed for assessing the potential exposure of residents and bystanders to pesticides through spray drift have highlighted the need for mitigation strategies to reduce exposure of members of the public. Drift-reducing equipment is readily available in many countries and is accepted as mitigation for the exposure of surface water to drifting pesticide sprays but there is concern that the drift-reduction measurement methods used to define the exposure of surface water might not be relevant to bystanders. Airborne spray is an important component in bystander exposure. Two wind tunnel experiments were undertaken to evaluate whether reductions in airborne spray are as great as the reductions in measured spray drift that occur using protocols designed to classify nozzles for protecting surface water. Results, with nozzles and pressures with a range of nominal drift reduction, and three different spray liquid types, suggested very strongly that the nominal drift reduction of a nozzle/pressure combination will give at least the same level of reduction in airborne spray for distances 3–5 m downwind. These data should be considered in the context of field data and model simulations in order to establish robust mitigation measures for regulatory exposure assessment. They indicate that the nominal drift reduction, measured using UK, Netherlands or German protocols, can be used to reduce bystander exposure up to 90%. The BREAM2 model for bystander exposure to spray drift can therefore be extended to include drift mitigation, with reductions in exposure up to 90% for classified equipment used in the appropriate way. Highlights: Wind tunnel experiments measured drift reduction and potential bystander exposure. Reduction in measured airborne spray was as great as the nozzle's drift classification. Results applied to UK, NL and DE classification systems and a range of formulations.